Placement Work Experience May Mitigate Lower Achievement Levels of Black and Asian vs. White Students at University - Moores, Elisabeth; Birdi, Gurkiran K.; Higson, Helen E. (Frontiers in Psychology, 2017)
Ethnic minority groups have been shown to obtain poorer final year degree outcomes than their majority group counterparts in countries including the US, the UK and The Netherlands. Obtaining a lower degree classification may limit future employment prospects of graduates as well as opportunities for higher level study. To further investigate this achievement gap, we analysed performance levels across three academic years of study of 3,051 Black, Asian and White students from a UK University. Analyses of covariance investigated effects of ethnicity and work placement experience (internships) on first, second and final year marks, whilst statistically controlling for a number of factors thought to influence achievement, including prior academic performance. Results demonstrated superior achievement of White students consistently across all years of study. Placement experience reduced, but did not eliminate, the size of the achievement gap exhibited by final year students. Sex, parental education and socioeconomic status had no significant main effects. Female students showed a more complex pattern of results than males, with Black females not showing the same final year uplift in marks as their Asian and White counterparts. Implications and possible explanations are discussed.